A Fresh Glimpse into Cartilage Immune Privilege. (December 2022) - Garrity, Carissa; Arzi, Boaz; Haus, Brian; Lee, Cassandra A.; Vapniarsky, Natalia
The increasing prevalence of degenerative cartilage disorders in young patients is a growing public concern worldwide. Cartilage's poor innate regenerative capacity has inspired the exploration and development of cartilage replacement treatments such as tissue-engineered cartilages and osteochondral implants as potential solutions to cartilage loss. The clinical application of tissue-engineered implants is hindered by the lack of long-term follow-up demonstrating efficacy, biocompatibility, and bio-integration. The historically reported immunological privilege of cartilage tissue was based on histomorphological observations pointing out the lack of vascularity and the presence of a tight extracellular matrix. However, clinical studies in humans and animals do not unequivocally support the immune-privilege theory. More in-depth studies on cartilage immunology are needed to make clinical advances such as tissue engineering more applicable. This review analyzes the literature that supports and opposes the concept that cartilage is an immune-privileged tissue and provides insight into mechanisms conferring various degrees of immune privilege to other, more in-depth studied tissues such as testis, eyes, brain, and cancer.